2022
DOI: 10.1101/2022.06.16.496437
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Generative Adversarial Networks Can Create High Quality Artificial Prostate Cancer Magnetic Resonance Images

Abstract: Purpose: Recent integration of open-source data to machine learning models, especially in the medical field, has opened new doors to study disease progression and/or regression. However, the limitation of using medical data for machine learning approaches is the specificity of data to a particular medical condition. In this context, most recent technologies like generative adversarial networks (GAN) could be used to generate high quality synthetic data that preserves the clinical variability. Materials and Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…In addition, they also found that for younger radiologists, this resulted in an improved ability to detect PCa. However, Xu and colleagues 105 found that a blinded radiologist did not find the quality of their synthetic images to be inferior to those non‐processed.…”
Section: Ai For Image Acquisitionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, they also found that for younger radiologists, this resulted in an improved ability to detect PCa. However, Xu and colleagues 105 found that a blinded radiologist did not find the quality of their synthetic images to be inferior to those non‐processed.…”
Section: Ai For Image Acquisitionmentioning
confidence: 99%
“…Deep learning has also been used in the emerging field of synthetic MRI, where generative adversial models create images based on acquired data 105 . Hu and colleagues 106 compared acquired DWI images to those modified by their model and found improved image quality with reduced distortion and artifacts.…”
Section: Ai For Image Acquisitionmentioning
confidence: 99%
“…Given its potential and its successes in medical image synthesis 3,[13][14][15][16] and, particularly, lesion region-of-interest generation, 15 we adopt the SinGAN architecture 17 to generate multiple synthetic images from a single training image. SinGAN is a multi-scale generative adversarial network (GAN) 18 containing a generator-discriminator pair in each scale.…”
Section: Single Image Generative Modelmentioning
confidence: 99%
“…In the context of PCa, these algorithms can be trained on data from tissue samples, medical images, and other clinical information to identify patterns and features associated with the disease [62][63][64][65][66][67][68][69][70][71][72] . Machine learning has proven to be particularly effective in the automated analysis of medical images, including MRI scans and biopsy slides [73][74][75][76][77][78][79][80][81][82] . These algorithms can accurately detect suspicious areas of the prostate and provide a more precise diagnosis than traditional manual analysis.…”
mentioning
confidence: 99%